Penerapan Media Kuis Berbasis Kahoot! Terhadap Minat Belajar Bahasa Arab Kelas XI IPA 5 SMAN 1 Dukupuntang - Maulana, Iman; Sidiq, Yogi Hasbi (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2023)
This study discusses the effect of Kahoot-based quiz media application on interest in learning Arabic in Dukupuntang 1 public high school. This study is a quantitative study with a pre-post test design. The tools used in this research are questionnaires and observations. The subjects of the study are XI IPA 5th grade students, a total of 15 students. Research data were analyzed using the t test. When t-test is included, t number = 9,244 and t tabel = 2,145 ie 9,244 > 2,145 at 5% significance level. H1 was accepted, that is, it is understood that the application of the kahoot-based quiz environment significantly affects the interest in learning Arabic. The mean N-value in the "Average" category is 0.33. The findings of this research provide additional options for teachers to use kahoot media in educational analysis.